Healthcare use according to deprivation among French Alzheimer's Disease and Related Diseases subjects: a national cross-sectional descriptive study based on the FRA-DEM cohort - Couret, Anaïs; Lapeyre-Mestre, Maryse; Renoux, Axel; Gardette, Virginie (Frontiers in Public Health, 2024)
Introduction A pluriprofessional and coordinated healthcare use is recommended in Alzheimer’s Disease and Related Diseases (ADRD). Despite a protective health system, France is characterized by persistent significant social inequalities in health. Although social health inequalities are well documented, less is known about social disparities in healthcare use in ADRD, in particular in France. Therefore, this study aimed to describe healthcare use according to socioeconomic deprivation among ADRD subjects, and the possible potentiating role of deprivation by age. Methods We studied subjects identified with incident ADRD in 2017 in the French health insurance database (SNDS). We described a large extent of their healthcare use during the year following their ADRD identification. Deprivation was assessed through Fdep, measured at the municipality level, and categorized in quintiles. We compared healthcare use according to the Fdep quintiles through chi2 tests. We stratified the description of some healthcare uses by age group (40-64, 65-74, 75-84, 85 and older), number of comorbidities (0, 1, 2-3, 4 comorbidities and more) or the presence of psychiatric comorbidity. Results 124,441 subjects were included. The most deprived subjects had lesser use of physiotherapy (28.56% versus 38.24%), ambulatory specialist (27.24% versus 34.07%), ambulatory speech therapy (6.35% versus 16.64%), preventive consultations (62.34% versus 69.65%) and were less institutionalized (28.09% versus 31.33%) than the less deprived ones. Conversely, they were more exposed to antipsychotics (11.16% versus 8.43%), benzodiazepines (24.34% versus 19.07%), hospital emergency care (63.84% versus 57.57%) and potentially avoidable hospitalizations (12.04% versus 10.95%) than the less deprived ones. Discussion and conclusion The healthcare use of subjects with ADRD in France differed according to deprivation index, suggesting potential health renunciation as in other diseases. These social inequalities may be driven by financial barriers, lower education levels contributing to health literacy (especially for preventive care). Further studies may explore them.